The essential New York Times cookbook : the recipes of record - Hesser, Amanda (W. W. Norton & Company, Inc., 2021)
"The James Beard Award-winning compendium of the paper's best recipes, revised and updated. Ten years after the phenomenal success of her once-in-a generation cookbook, former New York Times food editor Amanda Hesser returns with an updated edition for a new wave of home cooks. Devoted Times subscribers as well as newcomers to the paper's culinary mother lode will find dozens of recipes to treasure: Purple Plum Torte, David Eyre's Pancake, Pamela Sherrid's Summer Pasta, and a host of other classics, from 1940s Caesar Salad and 1960s flourless chocolate cake (Evelyn Sharpe's French Chocolate Cake) to today's No-Knead Bread and Giant Crinkled Chocolate Chip Cookies. Also included are fifty new but instantly iconic recipes, including Samin Nosrat's Herbed Rice with Tahdig, Melissa Clark's Simple Roast Turkey, and Alison Roman's one-pot Spiced Chickpea Stew. Hesser has tested and adapted each of the 1,000-plus recipes, and she highlights her go-to favorites from more than a century's-worth of cooking tradition with wit and warmth. As Saveur declared, this is a "tremendously appealing collection of recipes that tells the story of American cooking.""--